حركية البنيات الاسلوبية في الشعر المغاربي المعاصر - صالحي, سمية (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2022)
الملخص: لقد تمكنت الحركة الشعرية من وضع مقوماتها الخاصة ،حيث استطاعت ان تفرض وجودها وتصبغ عليه طابع الهوية المغاربية، وهذا بعد ظهور كوكبة من الشعراء الذي خاضوا غمار حركة الحداثة في الشعر ،حيث سعوا لتأسيس مبدأ التميز و الابداع ،وذلك بمنجزات تواكب مستجدات العصر و متغيراته ينطلق الشعر المغاربي المعاصر من مرجعية فكرية وحضارية متميزة باختلافاتها وتعددية مشاربها ، ذلك كون المنطقة المغاربية خاضت الكثير من المتغيرات الحضارية عبر الازمان ، كل هذه التجاذبات الحضارية صقلت الابداع الفني ،وطبعت عليه مميزات الخصوصية و التفرد ،تمثل اساسه واصالته ، ومن خلالها استشرف الشعراء مستقبل التطور الفكري و اخرجوه على شكل ابداعات تتسم بالرقي و الحركية في الشكل و المضمون،فالشعراء المغاربة تشبعوا بالموروث الثقافي الشعري ليكون لهم اهم المرجعيات الفاعلة الداعمة للتطور ، وذلك لم يتاتى الا بعد تغييب ودحظ كل فكرة سكونيةجامدة و أسسوا على أنقاضها مقومات التحرر والانعتاق الفكري ،فانجزوا نصوصا شعرية زاخرة بالحركية في كل مستوياتها اللغوية و الشكلية و الدلالية. Résumé :فرنسية أو انجلزية Abstract:Contemporary Maghreb literature has managed to draw its own path and define its own characteristics, within major historical transformations and within different civilizational currents, and this is due to the nature of the distinct geographical region that is always disputed, and it is known that it is a region that witnessed many historical periods, events, policies and ideologies that had a direct impact. Or indirectly in the nature of creativity, which at the beginning of his era did not receive proper attention But what is noticeable is this qualitative shift of contemporary Maghreb literature, in terms of privacy and distinction. Observing the cultural movement at the level of intellectual or philosophical production in the Arab Maghreb proves that these countries are in a state of movement and a great depth of artistic creativity. The contemplator of contemporary Maghreb poetics realizes the existence of a terminological apparatus dominated by indeterminacy. These poets have almost an advantage and a characteristic that distinguishes them, and one of the manifestations of this particularity is that it organizes a generative organization, bearing reproductive components, because the semantic energy inherent in the poetic text is the motivator of this generative force, leading to the opening of The doors of semantic possibility, and the expansion of the scope of linguistic expression in front of the reader to move in the space of the text a great movement that allows him to stand at the semantics that are not saturated intellectually, and thus enriches the text. Tracing the forms of this openness at the level of rhythm with its transgressions of weights, and in the lexical units replete with deviations and structural structures full of fluctuations, and in the semantic goals that are dominated by ambiguity, and its connection with the dynamism of the Maghreb poetic text puts us before the inevitability of the existence of new profound poetic texts around which the readings differ, and the images are multiple Its interpretations, and this is what gives it permanent mobility at the level of the creator during his systems, or at the level of the recipient through the plurality of his readings.
أطروحة دكتوراه تخصص أدب مغاربي في الأدب العربي
Keywords: الاسلوبية – الشعر المغاربي – الحركية; Maghreb literature - transformations